Kontroverze državljanstva in nastavki za opredelitev digitalnega državljanstva - Pajnik, Mojca (Teorija in praksa, 2014)
The article analyses citizenship that is understood as the activity and participation of citizens in debating matters of public concern. Our conceptualisation follows the politicality of citizenship that is discussed within a dialectic relationship of politicisation/depoliticisation. We first define political citizenship and then move on to discuss depoliticisation trends such as the nationalisation, commodification and mediatisation of citizenship. These trends, i.e. nationalisation, a reduction of citizenship to status, commodification, a reduction to the laws of market fundamentalism and mediatisation, and the triumph of consumerist non-citizenship, are analysed as antagonisms to a political conceptualisation. In discussing the controversies of citizenship, the article develops an attempt to define digital citizenship that follows endeavours to rehabilitate citizenship as a political concept, focusing on media and the digital sphere.
Keywords: Citizenship; Digital media; digitalno državljanstvo; Državljanstvo; Elektronski mediji; Informacijska tehnologija; Information technology; Political participation; Politična participacija